Knowledge of Speech and Language Therapists about Drugs Related to Speech, Language, Voice and Swallowing Disorders - Namık Yücel Birol; Esra Yaşar Gündüz; Samet Tosun (Revista de Investigación en Logopedia, 2024)
This descriptive study aims to assess the knowledge of speech and language therapists, who assess and treat clients with speech, language, voice, and swallowing disorders, their pharmacology education, and regarding the drugs related to these disorders. This study involved 96 speech and language therapists from different regions of Türkiye. A survey based on the literature was created to assess the level of knowledge of participants about the indications, contraindications and side effects of drugs related to speech, language, voice and swallowing disorders, as well as their pharmacology training. Our study determined that more than half of the participants had a low level or no knowledge about the indications, contraindications and side effects of drugs related to speech, language, voice and swallowing disorders. In addition, 86.5% of participants reported that they had not received adequate training on drugs at the bachelor and graduate level, and 93.8% of participants would like to receive more training on this subject. Since there is no study in literature that assesses the pharmacology knowledge of speech and language therapists, it is envisaged that our research will make a significant contribution to the field and raise the level of knowledge and awareness among professionals.